INSTAGRAM DIGITAL MARKETING STRATEGY FOR @BRIYANI MANDHI NUSANTARA PRODUCTS FOR INCREASING SALES - M. Faruq Khusen; Didik Hariyanto (Antis Publisher, 2024)
General Background: In the contemporary digital landscape, effective marketing strategies are crucial for business growth and product recognition. Specific Background: This research focuses on the digital marketing strategy employed by Briyani Mandhi Nusantara through Instagram, a platform that has become vital for engaging consumers in the food industry. Knowledge Gap: Despite the increasing significance of social media marketing, there is limited empirical evidence on how specific strategies on Instagram can directly influence sales in local food businesses. Aims: The primary aim of this study is to evaluate the effectiveness of Briyani Mandhi Nusantara’s Instagram marketing strategy in enhancing sales and brand visibility. Results: Utilizing qualitative methods—including interviews, observations, and documentation—this research reveals that Briyani Mandhi Nusantara effectively leverages various Instagram features, such as feed posts, Stories, Reels, and targeted hashtags. The application of the AIDA theory (Attention, Interest, Desire, Action) was instrumental in capturing consumer engagement and driving sales. Novelty: This study contributes to the existing literature by demonstrating a practical application of digital marketing theories in a local food context, offering insights into the nuances of Instagram as a marketing tool. Implications: The findings underscore the importance of tailored digital marketing strategies for local businesses and suggest that similar enterprises can enhance their visibility and sales by adopting structured approaches to social media marketing. This research not only fills a gap in the literature but also provides actionable insights for practitioners in the field.